AN ANALYSIS OF THE CREDIT SERVICE EARNINGS UPON THE BALANCE OF BUSINESS REVENUES AT THE CREDITS AND SAVINGS BUSINESS UNIT OF KPRI IN SUKABUMI - Nani Pujiastuti (STIE Binaniaga, 2018)
“An analysis of the Credit Service Earnings upon Balance of Business Revenues at the Credits and Savings Business Unit (SPU) of KPRI in Sukabumi”. This research has been done since the writer is interested in figuring out the problems about the earnings of credit services at KPRI in Sukabumi and the balance of business revenues (SHU) at KPRI in Sukabumi, as well as how to analyze the credit service earnings upon the balance of business revenues at the credits and savings business unit of KPRI in Sukabumi. However, this research is a quantitative study using a descriptive approach where the writer has been describing only the existing data using a qualitative description. Technique of data collection has applied field study research and library study. The result of the research has indicated that the earning of credit services at KPRI in Sukabumi has been increasing from year to year. The biggest increasing one was happened in 2009 which was Rp 846,979,876.00 higher than the previous year, and the smallest one was happened in 2012 which was Rp 231,494,441.00 less than the previous year. Nevertheless the balance of business revenue has been increasing from 2009 to 2011 but it has decreased in 2012. The biggest increasing one was happened in 2009 which was Rp 89,261,608.00 and it was decreased in 2012 which was Rp 18,352,811.00. The decreasing of this revenue was happened due to the total amount of business revenue had been received only from the credit units and other earnings. But , not any revenue of goods credit facilities had been received since there has not any transactions of goods selling been occured in 2012. Based on the analysis of the credit service earnings upon the balance of business revenues at KPRI in Sukabumi, it has indicated that the earnings of credit service has been relatively fluctuative each year. The contribution of the credit service earnings upon the balance of business revenue in 2008 was the biggest one which was 15.76% and the lowest one was in 2012 which was 1.79%.Key words: Credit, Saving, Service Earning, Business Revenue